Β-Blockers Increase the Risk of Being Born Small for Gestational Age or of Being Institutionalized During Infancy. Issue 3 (September 2015) - Xie, R.H.; Guo, Y.; Krewski, D.; Mattison, D.; Walker, M.C.; Nerenberg, K.; Wen, S.W.
Abstract : ( BJOG . 2014;121(9):1090–1096)